2017
DOI: 10.12928/pharmaciana.v7i2.6622
|View full text |Cite
|
Sign up to set email alerts
|

Antiobesity and antihypercholesterolemic effects of white tea (Camellia sinensis) infusion on high-fat diet induced obese rats

Abstract: ABSTRAKKondisi obesitas dapat menyebabkan metabolime lipid terganggu sehingga menjadi faktor resiko hiperkolesterolemia. Katekin dan epigallocatechin gallate dalam white tea berpotensi sebagai penghambat aktivitas enzim lipase. Senyawa kafein dan derivat katekin memiliki peran sebagai antihiperkolesterolemia. Penelitian ini bertujuan untuk melihat efek antiobesitas dan antihiperkolesterolemia dari seduhan white tea terhadap kadar lipase serum serta kolesterol total serum pada tikus yang diberi diet lemak tingg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 33 publications
0
4
0
Order By: Relevance
“…Meniran extract has been shown to increase macrophage phagocytic activity and nitric oxide production [4]. Many polyphenol compounds have been reported to have positive pharmacological effects [5][6][7]. In this case, the primary compound responsible for increasing the immune system is polyphenols, especially flavonoids [8].…”
Section: Introductionmentioning
confidence: 99%
“…Meniran extract has been shown to increase macrophage phagocytic activity and nitric oxide production [4]. Many polyphenol compounds have been reported to have positive pharmacological effects [5][6][7]. In this case, the primary compound responsible for increasing the immune system is polyphenols, especially flavonoids [8].…”
Section: Introductionmentioning
confidence: 99%
“…The results showed a difference in median body weight before and after being given a high-fat diet in each group as listed in Table 1. Bodyweight increased by more than 20%, which means that obesity has occurred [13], [14]. The results of statistical tests showed a significant difference in body weight before and after being given a high-fat diet in each group (p < 0.05).…”
Section: Resultsmentioning
confidence: 99%
“…The results of statistical tests on the difference in body weight at the beginning and at the end of the treatment showed that giving HFD could significantly increase the bodyweight of rats and could be reduced by orlistat, and the increase was inhibited by the provision of Bambu Tali tea (Table 2). Test animals are said to be obese if there is an increase in body weight> 20% of the initial body weight (Patonah et al, 2017;Shiyan et al, 2017;Yuniarto et al, 2015). In this study, HFD administration caused an increase in body weight of rats by 46%.…”
Section: Bambu Tali Tea Inhibited the Weight Gain Of Ratmentioning
confidence: 99%